Establishment of an Efficient System for Rhizome Proliferation and In Vitro Flowering Induction from Protocorm Explants in Cymbidium goeringii - Yongqi Zhi; Chenhao Wang; Yi Yang; Ming Chen; Muthusamy Ramakrishnan; Bo Fu; Lili Wang; Qiang Wei; Sen Wang (Horticulturae, 2025)
Unlike other orchids in the Orchidaceae family, Cymbidium goeringii presents significant challenges for in vitro flowering. In this study, through the screening of different basal media, hormone combinations, and other conditions, we developed efficient rhizome regeneration (micropropagation) and in vitro flowering induction systems from protocorm explants of C. goeringii hybrids. To obtain protocorm explants, seeds were pretreated with either NaOH or NaOCl. Our results indicated that NaOH pretreatment enhanced seed germination more effectively than NaOCl, and Knudson C medium proved more suitable for protocorm induction. The resulting protocorms were then used as primary explants for efficient rhizome micropropagation. An orthogonal design identified the optimal combination for rhizome proliferation: 9.0 mg/L 6-BA, 9.0 mg/L NAA, 3.0 mg/L IBA, and 0.1 g/L activated charcoal (Treatment 9), which achieved a proliferation rate of 35.17%. For rhizome differentiation, MS medium supplemented with 10 mg/L 6-BA, 0.1 mg/L NAA, and 0.1 mg/L AgNO3 (Treatment 6) achieved a 100% differentiation rate and produced 3.93 buds per explant. Building on this optimized micropropagation system, in vitro flowering was induced directly from rhizomes. The most effective medium was MS (1/3N, 3P) supplemented with 9.0 mg/L 6-BA, 0.1 mg/L NAA, and 0.1–0.3 mg/L TDZ (Treatment 6), resulting in a 36% flower bud induction rate and a 16% normal flower bud formation rate. Orthogonal analysis and ANOVA confirmed that 6-BA was the most significant factor influencing floral transition, with the low-nitrogen and high-phosphorus MS (1/3N, 3P) medium also being a key contributor. Consequently, our study has established an efficient rhizome micropropagation system that enables in vitro flowering induction in C. goeringii hybrids within just six months. This represents a substantial 60–80% reduction in the flowering time (from 6–7 years to 1–2 years), compared to the traditional 6–7-year cultivation period. Future work will focus on ex vitro acclimatization, detailed floral-trait validation, and hormone-regime refinement for fast-tracking breeding programs.